2011
DOI: 10.1016/j.bmcl.2011.09.095
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy studies of tRNA-T box antiterminator RNA complex in the presence of 1,4-disubstituted 1,2,3-triazoles

Abstract: The binding of tRNA to the T box antiterminator RNA element is a critical component of the T box riboswitch mechanism that regulates essential genes in many Gram-positive bacteria. A series of 1,4-disubstituted 1,2,3-triazoles was screened for disruption of the tRNA-T box antiterminator RNA interaction using a fluorescence anisotropy-based assay. Several compounds reduced the anisotropy greater than 50% likely indicating significant competition for binding antiterminator RNA. General structure-activity trends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…One potential site for small‐molecule intervention is the conserved seven‐nucleotide bulge of the T‐box anti‐terminator hairpin to which the 5′‐NCCA‐3′ terminus of unacylated tRNA binds. Neomycin B and a series oxazolidinone derivatives had been found to bind a 29‐nucleotide anti‐terminator model of the B. subtilis glyS T‐box . Binding at this site may impede proper transcription control by taking advantage of the stability (free energy) differences between the anti‐terminator and terminator T‐box elements .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential site for small‐molecule intervention is the conserved seven‐nucleotide bulge of the T‐box anti‐terminator hairpin to which the 5′‐NCCA‐3′ terminus of unacylated tRNA binds. Neomycin B and a series oxazolidinone derivatives had been found to bind a 29‐nucleotide anti‐terminator model of the B. subtilis glyS T‐box . Binding at this site may impede proper transcription control by taking advantage of the stability (free energy) differences between the anti‐terminator and terminator T‐box elements .…”
Section: Discussionmentioning
confidence: 99%
“…Neomycin Ba nd as eries oxazolidinone derivatives had been found to bind a2 9-nucleotidea nti-terminator model of the B. subtilis glyS T-box. [61][62][63][64][65][66] Binding at this site may impede Figure 7. PKZ18 cytotoxicity.a)Representative images of mouse macrophage-like J7 cells assayedfor cytotoxicity with PKZ18.…”
Section: Discussionmentioning
confidence: 99%
“…With the medium throughput fluorescence-monitored functional assay, multiple replicates of inhibition reactions and associated controls can be run simultaneously, thus facilitating the discernment of potentially subtle differences. The potential inhibitory effect of 1, 4-disubstutited 1, 2, 3-triazole 1 , which is known to bind the T box antiterminator RNA element and disrupt its interaction with tRNA [34,36], was investigated. Triazole 1 inhibited overall transcription, but with no significant additional inhibitory effect on the T box riboswitch (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In a single-round in vitro transcription assay, the T box riboswitch function was also modulated by oxazolidinones [32]. The oxazolidinone analogs, 1,4-disubstituted 1,2,3-triazoles, bind antiterminator model RNA in a structure-specific manner [33-35] and inhibit tRNA binding to antiterminator model RNA [36]. …”
Section: Introductionmentioning
confidence: 99%
“…More importantly, through the use of this assay, several 1,4‐disubstituted 1,2,3‐triazoles were identified that significantly altered the observed stability of the antiterminator model RNA AM1A in a structure‐dependent manner. A ligand‐induced Δ T m does not, a priori , indicate that the ligand will be effective at disrupting the tRNA‐antiterminator RNA complex; however, it is very intriguing that GHB‐7, one of the compounds with the greatest shift in T m , is also one of the compounds that resulted in the greatest disruption of the tRNA‐antiterminator complex in a fluorescence anisotropy assay (32). Further studies are in progress to characterize the interactions of the lead triazole compounds with AM1A to determine what specific structural features lead to stabilization or destabilization of the antiterminator model RNA.…”
Section: Discussionmentioning
confidence: 99%